Pengaruh Kompetensi Sumber Daya Manusia, PenerapanStandar Akuntansi Pemerintahan, dan Good GovernanceTerhadap Kualitas Laporan Keuangan (Studi Kasus Pada Dinas Pendapatan Pengelolaan Keuangan dan AsetDaerah (DPPKAD) Kabupaten Sragen) - Ubaidah, Tsaniya, Dra. Nursiam, M.H., Ak., CA (2017)
The study aimed to determine the effect of human resource competency, application of goverment accounting standard on quality, and implementation good governance on the quality of local government financial reporting reliability at Sragen Regency. This research uses quantitative method with primary data that collecting questionnaire. In the study the samples were 66 civil servants who are involved in the preparation of financial statements at DPPKAD of Sragen Regency. The sampling tehnique used is purposive sampling. Data analysis method used in this study was multiple linear regression analysis. The data obtained are then analyzed using SPSS 21.00. The result this research revelead that there was influence of human resource competency, application of goverment accounting standard on quality, and implementation good governance has effect on the quality of local goverment financial reporting reliability at DPPKAD of Sragen Regency.